Delta-Like 4 Activates Notch 3 to Regulate Self-Renewal in Skeletal Muscle Stem Cells. (27th December 2017) - Low, SiewHui; Barnes, Josephine L.; Zammit, Peter S.; Beauchamp, Jonathan R.
Abstract : Notch signaling is essential to maintain skeletal muscle stem cells in quiescence. However, the precise roles of different Notch receptors are incompletely defined. Here, we demonstrate a role for Notch3 (N3) in the self-renewal of muscle stem cells. We found that N3 is active in quiescent C2C12 reserve cells (RCs), and N3 over-expression and knockdown studies in C2C12 and primary satellite cells reveal a role in self-renewal. The Notch ligand Delta-like 4 (Dll4) is expressed by newly formed myotubes and interaction with this ligand is sufficient to maintain N3 activity in quiescent C2C12 RCs to prevent activation and progression into the cell cycle. Thus, our data suggest a model whereby during regeneration, expression of Dll4 by nascent muscle fibers triggers N3 signaling in associated muscle stem cells to recruit them to quiescence, thereby renewing the stem cell pool. Abstract : When induced to differentiate, skeletal muscle myoblasts express Notch 3 (N3) before fusing to form myotubes that express Delta-like 4 (Dll4). Dll4-dependent N3 activity maintains myoblasts in quiescence, inhibiting both proliferation and differentiation. As muscle regeneration is asynchronous, this suggests a model whereby nascent myotubes could recruit adjacent myoblasts into quiescence, regenerating both functional tissue and the stem cell compartment.